Evaluation of Darn Repair for Recurrence Rate in the Management of Indirect Inguinal Hernia - Hafiz Gul Nasib Khan, Muhammad Shoaib Khan, Atif Iqbal, Aamir Khan, Muhammad Amir Murtaza, Mohammad Basil Rizvi (Pakistan Journal of Medical & Health Sciences, 2023)
When an organ, or even part of an organ, protrudes through the inguinal canal, it is called an inguinal hernia. Two-thirds of all herniations are of the indirect inguinal subtype; they are most common in adults between 30 and 59; and men are twice as likely to be affected as women. The standard treatment for a hernia is surgery. A decrease in collagen metabolism and fibro-connective tissue in the groin is typically the root cause of an inguinal hernia. Both of these things cause the fascia transversalis to weaken. Because of this, surgeons have come up with a number of ways to strengthen the back wall of the inguinal canal. Methodology: Approximately 220 patients with indirect inguinal hernias participated in this descriptive study. The study collected data on the demographic characteristics of the patients, the clinical characteristics of the hernias, and the outcomes of the treatment. The results showed that the majority of the patients responded well to the treatment. The study also revealed that the incidence of hernia recurrence was low. Jinnah International Hospital Abbottabad and DHQ Battagram, Department of Surgery served as the study site for these individuals. Patients were followed for six months after therapy to check for problems or recurrence; darn repair was the modality of choice. Results: Results showed that darn repair had a low recurrence rate reported in the literature, despite some patients being lost to follow-up and others perceiving early complications like wound infection, seroma, hematoma formation, scrotal swelling, or prolonged postoperative pain. Restoring damaged tissues has also been shown to be less expensive than replacing damaged tissues with mesh. Tissue repair has showed potential and costs less than mesh repair for treating inguinal hernias, thus both options should be investigated. There is also a lower chance of infection with tissue repair compared to mesh repair Keywords: hernias,indirect inguinal hernia,darn repair,recurrence.